Usability Testing Essentials: Ready, Set... Test - Barnum, Carol M (Elsevier Science & Technology, 2010)
Usability Testing Essentials provides readers with the tools and techniques needed to begin usability testing or to advance their knowledge in this area.The book begins by presenting the essentials of usability testing, which include focusing on the user and not the product; knowing when to conduct small or large studies; and thinking of usability.